Pembentukan Bank Sampah Berkah (BSB) oleh Mahasiswa KKN Kelompok 67 Universitas Muhammadiyah Riau di Desa Lubuk Dalam - Fikri, Khusnul; Ikhsan, Mukhlis; Tamba, Nela Ardiansih; Fauziah, Dina; Habiburrahman (LPPM UMRI, 2023)
KKN is a form of student activity that involves serving the community. The purpose of this service activity is to socialize the creation of a waste bank by increasing public awareness of the importance of not littering. In addition, the waste bank is useful for all the people of Lubuk Dalam Village so they don't throw garbage or burn garbage, because from the garbage they can make money, crafts, etc., so they can boost the economy of the people in Lubuk Dalam Village. The method of implementing the activities was carried out through outreach to several schools and organizations in Lubuk Dalam Village. Through the